The Effects of Temperature on Clot Microstructure and Strength in Healthy Volunteers. (January 2016) - Lawrence, Matthew James; Marsden, Nick; Mothukuri, Rangaswamy; Morris, Roger H. K.; Davies, Gareth; Hawkins, Karl; Curtis, Daniel J.; Brown, Martin Rowan; Williams, Phylip Rhodri; Evans, Phillip Adrian
Abstract : BACKGROUND: Anesthesia, critical illness, and trauma are known to alter thermoregulation, which can potentially affect coagulation and clinical outcome. This in vitro preclinical study explores the relationship between temperature change and hemostasis using a recently validated viscoelastic technique. We hypothesize that temperature change will cause significant alterations in the microstructural properties of clot. METHODS: We used a novel viscoelastic technique to identify the gel point of the blood. The gel point identifies the transition of the blood from a viscoelastic liquid to a viscoelastic solid state. Furthermore, identification of the gel point provides 3 related biomarkers: the elastic modulus at the gel point, which is a measure of clot elasticity; the time to the gel point ( T GP ), which is a measure of the time required to form the clot; and the fractal dimension of the clot at the gel point, d f, which quantifies the microstructure of the clot. The gel point measurements were performed in vitro on whole blood samples from 136 healthy volunteers over a temperature range of 27°C to 43°C. RESULTS: There was a significant negative correlation between increases in temperature, from 27°C to 43°C, and T GP (r = −0.641, P < 0.0005). Conversely, significant positive correlations were observed for both the elastic modulus at the gel point (r = 0.513, P = 0.0008) and d f (r = 0.777, P < 0.0005) across the range of 27°C to 43°C. When temperature was reduced below 37°C, significant reductions in d f and T GP occurred at ⩽32°C (Bonferroni-corrected P = 0.0093) and ⩽29°C (Bonferroni-corrected P = 0.0317), respectively. No significant changes were observed when temperature was increased to >37°C. CONCLUSIONS: This study demonstrates that the gel point technique can identify alterations in clot microstructure because of changes in temperature. This was demonstrated in slower-forming clots with less structural complexity as temperature is decreased. We also found that significant changes in clot microstructure occurred when the temperature was ⩽32°C. Abstract : Supplemental Digital Content is available in the text.Published ahead of print October 5, 2015